PLACE OF PHOTODYNAMIC THERAPY IN ORGAN-SPARING TREATMENT PROGRAMS FOR SQUAMOUS CELL CARCINOMA OF THE ORAL MUCOSA - V. V. Polkin; M. A. Kaplan; V. S. Medvedev; D. Yu. Semin; V. N. Kapinus; I. S. Spichenkova; P. A. Isayev; D. N. Derbugov; A. M. Shubina (Опухоли головы и шеи)
The Medical Radiology Research Center Clinic performed photodynamic therapy (PDT) in 57 patients with cancer of the oral mucosa in the independent fashion. Pretreatment recurrent tumors were diagnosed in half (50.9 %) of the patients. Spectroscopy showed the therapeutic accumulation of the drug, which was 1.8–3 times greater than that in the skin and intact mucosa in the presence of a malignant neoplasm. Complete and partial tumor regression was achieved in 50 (87.7 %) and 4 (7 %)  patients, respectively; stabilization was seen in 3 (5.3 %) patients. Three-year overall survival was 86.7 ± 5.2 % and three-year relapse-free survival was 70.5 ± 7.1 %. PDT has an organ-saving directionality, without causing functional and cosmetic impairments, thus showing its rather high effectiveness.